A study of EFL anxiety of male and female high school students in chilean classrooms in-class lessons during the coronavirus pandemic - Fuentealba Mendoza, Macarena del Pilar (Universidad de Santiago de Chile, 2022)
Integrantes: Macarena del Pilar Fuentealba Mendoza, Nicole Daney Pérez Flores, Nicolás Esteban Romero Cáceres, Selena Fernanda Silva Quintanilla
Keywords: Estudiantes de educación media - Investigaciones - Chile - Actitudes; Inglés - Enseñanza - Hablantes extranjeros - Metodología; Ansiedad